Long-Term Paracetamol Treatment Impairs Cognitive Function and Brain-Derived Neurotrophic Factor in Adult Rat Brain - Laddawan Lalert; Nutnicha Tantarungsee; Tipthanan Chotipinit; Wilawan Ji-au; Anan Srikiatkhachorn; Supang Maneesri-le Grand (My University, 2023)
Paracetamol (acetaminophen, APAP) is known as a safe pain reliever; however, its negative effects on the central nervous system have gradually been reported. We examined alterations in learning and memory, and brain-derived neurotrophic factor (BDNF) expression in the frontal cortex and hippocampus at different durations of APAP treatment in rats. Novel object recognition (NOR) and Morris water maze (MWM) paradigms were used to assess learning and memory in rats fed with 200 mg/kg APAP at single-dose, 15-day or 30-day treatments. BDNF expression was evaluated through immunohistochemistry and Western blotting. The single-dose APAP treatment did not alter the NOR performance. However, deficits in the NOR and MWM capacities were detected in the rats with longer durations of APAP treatment. An analysis of BDNF expression revealed no significant change in BDNF expression in the single-dose APAP treatment, while rats given APAP for extended periods as treatment showed a significant decrement in this protein in the frontal cortex and hippocampus. Short-term APAP treatment has no effect on learning and memory, or BDNF expression; however, long-term APAP exposure causes cognitive impairment. The diminishment of the BDNF level in the frontal cortex and hippocampus due to the long period of treatment with APAP may at least in part be involved in altered learning and memory in rats.
Keywords: Nerve injury and regeneration